2014
DOI: 10.1136/archdischild-2014-306211
|View full text |Cite
|
Sign up to set email alerts
|

Tongue-tie and frenotomy in infants with breastfeeding difficulties: achieving a balance

Abstract: Good assessment and selection are important because 50% of breastfeeding babies with ankyloglossia will not encounter any problems. We recommend 2 to 3 weeks as reasonable timing for intervention. Frenotomy appears to improve breastfeeding in infants with tongue-tie, but the placebo effect is difficult to quantify. Complications are rare, but it is important that it is carried out by a trained professional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 40 publications
0
92
0
10
Order By: Relevance
“…Currently, there is a debate on how best to manage young infants with tongue-tie who have breastfeeding problems [5, 7, 26, 28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a debate on how best to manage young infants with tongue-tie who have breastfeeding problems [5, 7, 26, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Martinelli et al in 2015 demonstrated that, after a lingual frenotomy, babies with a short lingual frenulum show changes that favour the appropriate standards of breastfeeding and all the symptoms reported by the mothers improved [2]. Furthermore, Power and Murphy in 2015 conclude that 50% of the breastfed babies with ankyloglossia will not encounter any problems [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant tongue‐tie in breastfeeding pairs was overlooked during the second half of the 20th century. Tongue‐tie (and the newer diagnoses of upper lip tie and posterior tongue‐tie) have received increased attention following the resurgent commitment of women to breastfeeding over the past decade and the growth in numbers of breastfeeding support professionals 1 , 5 …”
Section: Boxmentioning
confidence: 99%
“…A systematic review of the literature in 2013 identified long-term improvement in breastfeeding in more than 50% of cases 3 . Moreover complications from the procedure are reported to be uncommon 4 and rare in our experience at Torbay Hospital.…”
mentioning
confidence: 72%